حركة الترجمة في العصر العثماني: مقارنة نقدية لعصري الازدهار والانحطاط ................................................. Translation in the Ottoman Period: a Comparative Critique of Periods of Progress and Decline - خان, شير علي (الدراسات الإسلامية, 2018)
This paper deals with the translation activity in the Ottoman Empire. It focuses on the translations done from Arabic, Persian, and other European languages to Turkish language and vice versa. Written and oral translations were the only means of communication between the Turkish Kings and Christian Byzantine rulers. Translation played a positive role by supplying the religious, literary and diplomatic heritage to Turkish which enriched the Turkish language on the one hand, and widened the intellectual, political and religious vision of the Turkish Sultans on the other. The Kings personally took interest in the translations of books. They appointed translators for translation and diplomatic interpretation, and in the later period they also established a school for the training of translators.